Pengembangan Perangkat Layanan Bimbingan Klasikal Untuk Meningkatkan Keterampilan Komunikasi Antarpribadi - Maria Fatima Selenda; I Ketut Gading; Kadek Ari Dwiarwati (Universitas Pendidikan Ganesha, 2022)
This study was aimed to determine the prototype, acceptability, and effectiveness of classical guidance service tools to improve interpersonal communication skills of vocational students. This device is a guideline for guidance and counseling teachers in providing counseling services in schools. By using the 4-D development research procedure proposed by Thiagarajan, then an acceptability assessment of the device was carried out by 5 experts in the field of guidance and counseling. The 47-point assessment instrument for each device, namely: (RPL, Materials, Media, LKPD and evaluation tools) refers to the acceptability of the device. The validity analysis uses the Content Validity Ratio (CVR) calculation formulation from Lawse, which shows the content validity (CVI) of 0.7-1 and is categorized as very good or special. This shows that the classical guidance service tool developed has met the eligibility criteria. The effectiveness test involved 50 students in the experimental class and 25 in the control class. This study uses a control group pre-test, post-test design method. The effectiveness test using the t test states that the development of classical guidance service tools is effective for improving interpersonal communication skills. Penelitian ini ditujukan untuk mengetahui prototype, keberterimaan, dan efektivitas perangkat layanan bimbingan klasikal untuk meningkatkan keterampilan komunikasi antarpribadi siswa SMK. Perangkat ini adalah pedoman bagi guru bimbingan dan konseling dalam memberikan layanan konseling disekolah. Dengan menggunakan prosedur penelitian pengembangan 4-D yang dikemukan oleh Thiagarajan, kemudian dilakukan penilian keberterimaan perangkat dinilai oleh 5 pakar dalam bidang bimbingan dan konseling. Instrumen penilian 47 butir dari masing-masing perangkat, yakni: (RPL,Materi, Media, LKPD dan Alat evaluasi) mengacu pada keberterimaan perankat. Analisis validitas menggunakan formulasi perhitungan Content Validity Ratio(CVR) dari Lawse, yang menunjukan validitas isi (CVI) sebesar 0,7-1 dan dikategorikan sangat baik atau istimewa. Hal ini menunjukan bahwa perangkat layanan bimbingan klasikal yang dikembangkan telah memeuhi kriteria kelayakan. Uji efektivitas melibatkan 50 siswa 25 orang kelas eksperimen dan 25 orang kelas control. Penelitian ini menggunakan metode control group pre-test, post-test design. Uji efektivitas menggunakan uji t menyatakan bahwa pengembangan perangkat layanan bimbingan klasikal efektif untuk meningkatkan keterampilan komunikasi antarpribadi.